Schema therapy with exposure and response prevention for the treatment of chronic anxiety with comorbid personality disorder. (15th December 2020) - Peeters, Nancy; Stappenbelt, Sylvie; Burk, William J.; van Passel, Boris; Krans, Julie
Abstract : Background and objectives: A considerable group of patients with anxiety disorders do not respond to guideline CBT treatment, possibly due to comorbid personality disorder (PD) traits. Schema therapy (ST) is an integrative treatment for personality disorders, and preliminary evidence suggests that it also affects anxiety. The present study examined the effects of a combination treatment ('SCHerp': ST + exposure and response prevention) in a non‐responsive outpatient group suffering from chronic anxiety and comorbid cluster C personality disorder. Methods: Psychological malfunction ( n = 42), and adaptive and maladaptive schema modes ( n = 49) were assessed pre‐ and post‐treatment. Results: Patients showed statistically significant decreases in psychological malfunction and maladaptive modes, and significant increases in adaptive modes from pre‐ to post‐treatment. Changes in modes were correlated with changes in psychological malfunction. Limitations: No control group or follow‐up measurements were included. Conclusions: The combination of ST and exposure with response prevention may be a viable avenue for research and treatment for this subpopulation. However, further research is needed to confirm and enhance effectiveness and identify working mechanisms of SCHerp. Practitioner points: The SCHerp programme combines schema therapy with exposure and response prevention to tackle chronic anxiety in patients with comorbid personality disorder SCHerp significantly reduced psychological malfunction and maladaptive modes, and increased adaptive modes Changes in schema modes correlated with changes in psychological malfunction, suggesting that schema modes are an appropriate treatment target in this population No active control group was included so no therapy‐specific factors can be determined at this stage